Aligning with Patients and Families: Exploring Youth and Caregiver Openness to Pediatric Headache Interventions - Allison M. Smith; Zoë J. Schefter; Hannah Rogan (MDPI AG, 2022)
Primary headache disorders are common yet underestimated in youth, resulting in functional disability, decreased quality of life, and caregiver burden. Despite the ubiquity of options, adherence remains challenging for families. One potential factor impacting willingness to engage in recommended treatments is openness. This study explored openness to multidisciplinary headache interventions and the relationships with demographic, pain-related, and psychological variables, among youth and their caregivers. Participants (n = 1087) were youth/caregiver dyads presenting for initial headache evaluation. They completed assessments of openness to headache treatments, medical information, functional disability, and pain-related distress. Overall openness was moderately high for youth and caregivers, and highly correlated between them (r = 0.70). Relationships between youth/caregiver openness to specific interventions were moderate-high (r = 0.42-0.73). These were stronger for interventional techniques but weaker for lifestyle changes. In hierarchical regression models predicting youth and caregiver openness, we found that counterpart openness accounted for the largest portion of variance in their own openness (31-32%), beyond demographic (3%), pain-related (10%), and psychological variables (2-3%). Our findings highlight the importance of involving caregivers in pediatric headache management, given their influence on youth openness and potential involvement in adherence. Awareness of youth/caregiver openness may guide clinicians providing recommendations.